Simiolus : Netherlands quarterly for the history of art. (Utrecht : Stichting Nederlandse Kunsthistorische Publicaties, 1966)
Simiolus is an English-language journal devoted to the history of Dutch and Flemish art of the fifteenth to seventeenth centuries, with occasional forays into more recent periods and other schools. Founded in 1966 as an outlet for art history students at the University of Utrecht, it has grown to become an internationally recognized journal of record in its field, publishing contributions by many renowned scholars and promising young art historians. (www.simiolus.nl)
Https://simiolus.nl/ The Simiolus index 1966–2021
Online: www.jstor.org (login)
Engels
Tijdschriften
Keywords: 15de eeuw; 16de eeuw; 17de eeuw; Nederlanden